Hepatitis C infection and outcomes in the Scottish haemophilia population. (20th June 2013) - Khan, M. M.; Tait, R. C.; Kerr, R.; Ludlam, C. A.; Lowe, G. D. O.; Murray, W.; Watson, H. G.
Summary: Patients with bleeding disorders previously frequently became infected with hepatitis C virus. We identified the number of patients infected in Scotland and assessed several aspects of the outcomes of HCV infection and its treatment comparing these with cohorts infected for other reasons. We calculated the number of individuals infected in Scotland (cohort A) starting with the total number of patients treated in Scottish haemophilia centres registered on the UKHCDO database between 1970 and 1989. Cases were then removed or added based on additional information from centre records. A second cohort B, consisted of 255 patients from cohort A and 47 patients HCV infected outside Scotland, but with follow‐up data from Scottish centres around their HCV infection. We estimate that 455 patients with bleeding disorders became infected by coagulation factor provided by NHS Scotland. In 302 individuals with documented HCV infection, rates of natural clearance (17.4%), genotype spread (64% genotype 1) and responses to antiviral therapy (14.5% with monotherapy; 38.8% with combination therapy) were similar to those in other cohorts. Thirty‐four liver biopsies were performed without adverse event and liver transplantation has been performed in 11 patients, seven for liver failure, four for hepatocellular carcinoma. Around 455 patients with bleeding disorders became HCV infected in Scotland before 1989. The natural history of HCV infection and responses to treatment are similar to those in other HCV‐infected cohorts. Liver transplantation has been used successfully for the treatment of end‐stage liver failure and hepatocellular carcinoma.